Cynaropicrin and inhibition of NF-κB activation: A structure activity relationship study. Issue 12 (15th June 2019) - Li, Jing; Yoshida, Yusuke; Kurita, Manami; Usuki, Toyonobu
Graphical abstract: Abstract: Cynaropicrin is a guaianolide sesquiterpene lactone with a 5-7-5 tricyclic skeleton, four exo-olefins, and two hydroxyl groups. This natural product has various biological activities including anti-inflammatory properties and antitrypanosomal activity. It was also found to suppress photoaging of the skin by inhibiting the transcription activity of nuclear factor-kappa B (NF-κB). In this paper, nine chemical derivatives of cynaropicrin were prepared, and the structure activity relationship (SAR) study for NF-κB inhibition by measuring relative light units (RLU) was conducted.